2020
DOI: 10.1097/aln.0000000000003256
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex versus Neostigmine for Reversal of Neuromuscular Blockade and Postoperative Pulmonary Complications (STRONGER)

Abstract: Background Five percent of adult patients undergoing noncardiac inpatient surgery experience a major pulmonary complication. The authors hypothesized that the choice of neuromuscular blockade reversal (neostigmine vs. sugammadex) may be associated with a lower incidence of major pulmonary complications. Methods Twelve U.S. Multicenter Perioperative Outcomes Group hospitals were included in a multicenter observational matched-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
236
4
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 214 publications
(255 citation statements)
references
References 36 publications
12
236
4
3
Order By: Relevance
“…Recent multicenter trials revealed that sugammadex defiantly decreased postoperative pulmonary complications in 45,712 adult patients undergoing noncardiac surgery [ 105 ]. The incidence of postoperative pulmonary complications such as pneumonia, respiratory failure, and pneumothorax was lower in the sugammadex group than that in the neostigmine group (3.5% vs. 4.8%; odds ratio, 0.70; 95% confidence interval, 0.63–0.77).…”
Section: Recent Clinical Interests Regarding Sugammadexmentioning
confidence: 99%
“…Recent multicenter trials revealed that sugammadex defiantly decreased postoperative pulmonary complications in 45,712 adult patients undergoing noncardiac surgery [ 105 ]. The incidence of postoperative pulmonary complications such as pneumonia, respiratory failure, and pneumothorax was lower in the sugammadex group than that in the neostigmine group (3.5% vs. 4.8%; odds ratio, 0.70; 95% confidence interval, 0.63–0.77).…”
Section: Recent Clinical Interests Regarding Sugammadexmentioning
confidence: 99%
“…Recovery of muscle tone affects the diaphragm, upper respiratory strength, and chest wall strength, and may also improve coughing ability, attenuate secretions, reduce alveolar collapse (associated with pneumonia), and prevent microaspiration [31,32]. A recent multicenter matched cohort study showed that sugammadex can reduce the likelihood of postoperative pneumonia compared to neostigmine [33].…”
Section: Discussionmentioning
confidence: 99%
“…Contraindications include but are not limited to a nonfasted state, achalasia, difficult airway, gastric outlet or bowel obstruction, gastroparesis, ileus, impaired swallowing, morbid obesity, and pregnancy. Of note, the use of sugammadex instead of neostigmine to reverse muscle relaxation was associated with a 30%-50% lower risk of postoperative pneumonia and respiratory failure in a recent large multi-center study, suggesting that incomplete reversal of muscle relaxant may play a larger role than previously recognized in pulmonary complications including aspiration [23].…”
Section: Risk Factors For Laryngospasmmentioning
confidence: 95%